2017
DOI: 10.4236/as.2017.89075
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Ancestral History of the German Angler and the Red-and-White Dual-Purpose Cattle Breeds Assessed through Pedigree Analysis

Abstract: Local cattle breeds continue to decline in numbers partly due to the use of high performing breeds in advanced production systems where genetic material of elite animals is widely spread. The objective of this study was to assess the within and across breed genetic diversity of the Angler and Red-andWhite dual-purpose (DP) cattle breeds applying different inbreeding concepts. Classical and ancestral inbreeding coefficients were computed from pedigree data using the gene dropping method. Effective population si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
30
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 24 publications
7
30
4
Order By: Relevance
“…The ancestral history coefficient has been only rarely studied yet. Our estimated values were higher for all birth-year groups than published for Angler and Red-and-White cattle breeds [ 33 ]. The tendencies of the estimated correlations of the different inbreeding parameters in our study were similar to those of reported for Angler and Red-and-White cattle [ 33 ].…”
Section: Discussioncontrasting
confidence: 62%
“…The ancestral history coefficient has been only rarely studied yet. Our estimated values were higher for all birth-year groups than published for Angler and Red-and-White cattle breeds [ 33 ]. The tendencies of the estimated correlations of the different inbreeding parameters in our study were similar to those of reported for Angler and Red-and-White cattle [ 33 ].…”
Section: Discussioncontrasting
confidence: 62%
“…Since year 2006 candidates’ plateaus are reflected from mostly female candidates, which show a stronger genetic relation (Figure ) and smaller variation of NC itself (Figure ). Moreover, the influence of RH as one major migrant breed (Table ) has been confirmed and is in accordance with the studies from Addo et al () and Schäler et al ().…”
Section: Discussionsupporting
confidence: 91%
“…Especially, small local breeds often reveal a poor pedigree quality. In case of the RDP, the pedigree file showed large gaps and a high rate of incompleteness regarding dams as mentioned by Addo, Schäler, Hinrichs, and Thaller () and Schäler et al (). In addition, different amounts of migrant breeds’ contribution (Table ), distinct NC variations per cohort (Figure ), and a low correlation between NC PED and NC SEG (Table ) strengthen previous assumptions.…”
Section: Discussionmentioning
confidence: 71%
“…In the first case, it is difficult to quantify the level of overestimation, however, restricting the number of considered generations is expected to increase the bias. In the latter case, recent genealogical studies have shown wide ranges in amount of pedigree knowledge and unbalanced pedigree, with EqG and percent of unknown parents ranging from < 2 to more than 10 generations, and from 0 to more than 30% respectively (Leroy et al 2006(Leroy et al , 2013Bartolomé et al 2011;Santana et al 2016;Addo et al 2017;Kumpulainen et al 2017). From our simulations, genealogies with more than 10% of unknown parents are expected to provide N e estimates with substantial overestimations regardless of the metrics chosen, and we may, nevertheless, recommend to restrict the number of generations considered for N e estimation in order to limit the extent of bias.…”
Section: Discussionmentioning
confidence: 99%